Assessment of the ergonomic design of diagnostic ultrasound transducers through wrist movements and subjective evaluation - Paschoarelli, Luis Carlos [UNESP]; de Oliveira, Ana Beatriz; Cote Gil Coury, Helenice Jane (Elsevier B.V., 2008)
This study presents procedures for assessing the redesign of ultrasound transducers. Wrist movements were recorded using elect rogoniometers. Perceptions of discomfort and acceptability of the new transducers were evaluated. The assessment was performed in two phases: (1) design of the product and an initial evaluation of movements during simulated activity with one mock-up and with two commercially available transducers; (2) project review and the development and evaluation of new mock-ups (2 and 3) by non-experienced subjects, and subjective assessment of all the mock-ups and commercial transducers by non-experienced subjects and trained physicians. First mock-up did not present improvements regarding the wrist movements and the time spent within safe amplitudes. The project review resulted in two new mock-ups that led to lower average amplitudes of movements (p <= 0,05) and more time spent within safe amplitudes. Thus, the application of quantitative (recording movements) and subjective (perceptions of discomfort and acceptability) approaches allowed for subsequent redesigns of the transducers that led to improvement of the product under evaluation.
Keywords: Usability; Redesign; Electrogoniometry; Acceptability; Discomfort; Ultrasonography